Lesion Index–Guided Ablation Facilitates Continuous, Transmural, and Durable Lesions in a Porcine Recovery Model. (April 2018) - Whitaker, John; Fish, Jeffrey; Harrison, James; Chubb, Henry; Williams, Steven E.; Fastl, Thomas; Corrado, Cesare; Van Zaen, Jérôme; Gibbs, Jennifer; O'Neill, Louisa; Mukherjee, Rahul; Rittey, Dianna; et al.
Abstract : Background: The Lesion Index (LSI) is a proprietary algorithm from Abbott Medical combining contact force, radiofrequency application duration, and radiofrequency current. It can be displayed during ablation with the TactiCath contact force catheter. The LSI Index was designed to provide real-time lesion formation feedback and is hypothesized to estimate the lesion diameter. Methods and Results: Before ablation, animals underwent cardiac computed tomography to assess atrial tissue thickness. Ablation lines (n=2–3 per animal) were created in the right atrium of 7 Göttingen mini pigs with point lesions (25 W). Within each line of ablation, the catheter tip was moved a prescribed distance (D/mm) according to 1 of 3 strategies: D=LSI+0 mm; D=LSI+2 mm; or D=LSI+4 mm. Two weeks after ablation, serial sections of targeted atrial tissue were examined histologically to identify gaps in transmural ablation. LSI-guided lines had a lower incidence of histological gaps (4 gaps in 69 catheter moves, 5.8%) than LSI+2 mm lines (7 gaps in 33 catheter moves, 21.2%) and LSI+4 mm lines (15 gaps in 23 catheter moves, 65.2%, P <0.05 versus D=LSI). ΔLSI was calculated retrospectively as the distance between 2 adjacent lesions above the mean LSI of the 2 lesions. ΔLSI values of ⩽1.5 were associated with no gaps in transmural ablation. Conclusions: In this model of chronic atrial ablation, delivery of uninterrupted transmural linear lesions may be facilitated by using LSI to guide catheter movement. When ΔLSI between adjacent lesions is ⩽1.5 mm, no gaps in atrial linear lesions should be expected. Abstract : Supplemental Digital Content is available in the text.